Entrepreneurship Education Shapes Entrepreneurial Intentions through Religiosity and Self-Efficacy - Rici Solihin; Suryana Suryana; Chairul Furqon; Mokh Adib Sultan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Enhancing entrepreneurial intention is a significant aspect in encouraging the emergence of new entrepreneurs, especially in overcoming economic and social challenges in the era of global competition. This study aims to investigate the effect of entrepreneurship education on entrepreneurial intentions, while considering the mediating roles of religiosity and self-efficacy. This study emphasizes a comprehensive investigation of the key factors that influence entrepreneurial intentions. This study employs a quantitative approach with 264 respondents from diverse educational and religious backgrounds. Data were collected using a validated Likert-scale questionnaire measuring entrepreneurship education, religiosity, self-efficacy, and entrepreneurial intention, and analyzed using SEM-PLS. The levels of entrepreneurship education, self-efficacy, religiosity, and entrepreneurial intention among students in Bandung were positive. These findings confirm that entrepreneurship education has a positive influence, both directly and indirectly, on entrepreneurial intentions through the mediating role of self-efficacy and religiosity. This research makes a significant contribution to the field of entrepreneurship education. These findings are expected to serve as practical guidance for educational institutions and policymakers in formulating strategies to increase entrepreneurial intent by strengthening entrepreneurship education, developing self-efficacy, and fostering religiosity.